ExlP induction of efficient RNAi loaded exosome production by stem cells:a novel tool for gene therapy. - A Ali, Syed (Universiti Sains Malaysia, 2016)

(untitled)
Alteration of gene expression plays important roles in disease inception. Controlling the expression of diseases-related genes may be used as treatment modality. Regulation of gene expression through RNA interference (RNAi) by using shRNA is well-established. However, absence of appropriate delivery vehicles has impeded the development of RNAi into a viable therapeutic modality.